A polar‐localized iron‐binding protein determines the polar targeting of Burkholderia BimA autotransporter and actin tail formation. (31st October 2014) - Lu, Qiuhe; Xu, Yue; Yao, Qing; Niu, Miao; Shao, Feng
Summary Intracellular bacterial pathogens including Shigella, Listeria, Mycobacteria, Rickettsia and Burkholderia spp. deploy a specialized surface protein onto one pole of the bacteria to induce filamentous actin tail formation for directional movement within host cytosol. The mechanism underlying polar targeting of the actin tail proteins is unknown. Here we perform a transposon screen in Burkholderia thailandensis and identify a conserved bimC that is required for actin tail formation mediated by BimA from B. thailandensis and its closely related pathogenic species B. pseudomallei and B. mallei. bimC is located upstream of bimA in the same operon. Loss of bimC results in even distribution of BimA on the outer membrane surface, where actin polymerization still occurs. BimC is targeted to the same bacterial pole independently of BimA. BimC confers polar targeting of BimA prior to BimA translocation across bacterial inner membrane. BimC is an iron‐binding protein, requiring a four‐cysteine cluster at the carboxyl terminus. Mutation of the cysteine cluster disrupts BimC polar localization. Truncation analyses identify the transmembrane domain in BimA being responsible for its polar targeting. Consistently, BimC can interact with BimA transmembrane domain in an iron binding‐dependent manner. Our study uncovers a new mechanism that determines the polar distribution of bacteria‐induced actin tail in infected host cells.